Pengaruh Sertifikasi Halal, Persepsi Harga, dan Lokasi Terhadap Keputusan Pembelian Konsumen Ayam Geprek SA’i Tlogomas - Evaliana, Silvia; Susyanti, Jeni; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The objective of the study is to determine how halal certification, cost, and location affect the decisions made by customers to buy geprek sa'i tlogomas chicken.  In this study, a quantitative research method is used. Following this Malhotra methodology, a sample of 70 respondents was selected from among all customers who had purchased Ayam Geprek Sa'i Tlogomas in Lowokwaru District, Malang City.  This study employs SPSS analysis tools in conjunction with multiple linear regression analysis.  The F and t tests are used in hypothesis testing. The output of the study present that the influence of halal certification, price and location have a significant simultaneous effect on the purchase decision of consumers of geprek sa'i tlogomas chicken. Halal certification variables, prices and locations have a significant effect on the purchase decision of consumers of geprek sa'i tlogomas chicken. Keywords: Halal Certification, Price, Location and Purchase Decision